Zeolite a preparation from high alumina fly ash of china using alkali fusion and hydrothermal synthesis method. (22nd March 2019) - Guozhi, Lu; Zhang, Tingan; Cheng, Chu; Zhang, Weiguang; Wang, Long; Wang, Yanxiu; Zhang, Zimu
Abstract: The preparation of zeolite A from high alumina fly ash (HAFA) of China has been carried out using the alkali fusion and hydrothermal synthesis method with the consideration of comprehensive utilization of the alumina and silica contents in HAFA. The pre-roasting, acid leaching, alkali fusion and hydrothermal synthesis experiments were carried out at varying factor values of temperature, silica to alumina mass ratio, NaOH concentration and time. The mullite is activated constantly with the increasing of calcination temperature before 850 °C in the pre-roasting process, and the iron content in the roasted ore can be decreased to 0.54% through the pre-roasting and acid leaching treatment. The zeolite A product can be prepared using HAFA with the optimal conditions of the alkali fusion temperature at 850 °C, the Si/Al in raw material at 0.8, the alkali concentration in hydrothermal synthesis at 2.5 mol L −1, the crystallizing temperature at 90 °C with 18 h holding time. The surface area of prepared zeolite A product is lower than that of standard sample due to the existing of impurities and heterocrystal. However, the thermal stability and surface area of prepared zeolite meet the requirement of zeolite molecular sieve. The valuable and comprehensive utilization of alumina and silica in HAFA from China can be achieved through the alkali fusion and hydrothermal synthesis treatment.